UNLOCKING COGNITIVE POTENTIAL: ENHANCING PROBLEM-SOLVING ABILITIES THROUGH INNOVATIVE PROBLEM-BASED LEARNING MODELS - Triani, Elza; Oktami, Listyana; Inghug, Delicia; Rizqiyah, Nabila Nur (EduFisika: Jurnal Pendidikan Fisika, 2024)
In this context, this literature review article aims to analyze how PBL can be a strong foundation in developing students' problem solving skills in the realm of science learning, as well as highlighting practical implications for education in the future. This research method uses qualitative. The data collection technique uses literature study, which is a technique used to collect data and theoretical and research sources related to the topic raised in a study. Types of secondary data obtained from published articles related to the PBL learning model in improving students' science problem solving skills. The analysis technique is carried out using a synthetic matrix. This research procedure begins with determining article search keywords, searching for literature articles on Goggle Scholar, selecting articles according to keywords, and analyzing the articles and their findings. The conclusion from the results of the literature study carried out regarding how the problem based learning model has an impact on students' problem solving skills in science learning is that by implementing this problem based learning model it will improve students' problem solving skills. This is proven by the results of 10 studies that have been analyzed.